2000
DOI: 10.1007/s003800070034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a phosphodiesterase III inhibitor on circulating blood volume after cardiopulmonary bypass

Abstract: Using a new method based on pulse dye densitometry, circulating blood volume (BV) was measured without direct sampling in patients undergoing open-heart surgery, and the effects of phosphodiesterase (PDE) III inhibitor administration during cardiopulmonary bypass (CPB) were evaluated. Sixteen patients scheduled for elective coronary artery bypass grafting were randomly assigned to the PDE III inhibitor group or control group. BV was determined before CPB, and immediately, and 4 and 12h after operation. After d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Although several methods exist for measuring circulating blood volume, using for example hydroxyethyl starch or a radioactive isotope, 10,20 pulse dye densitometry is noninvasive and reliable. 6 The combination of these 2 methods enables a simple and straightforward determination of capillary leakage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several methods exist for measuring circulating blood volume, using for example hydroxyethyl starch or a radioactive isotope, 10,20 pulse dye densitometry is noninvasive and reliable. 6 The combination of these 2 methods enables a simple and straightforward determination of capillary leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The ICG concentration was plotted semilogarithmically and extrapolated back to the mean transit time point to determine the initial ICG concentration, from which blood volume was calculated. 6 Blood volume was determined preoperatively, immediately after surgery, 2, 4, 6, 12, and 24 hours postoperatively, and on the 7 th postoperative day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Milrinone (0.5 µg·kg -1 ·min -1 infusion, no loading) may also be effective in restoring peripheral circulation after cardiac surgery [125] . A single bolus (1 or 1.5 mg/kg) of amrinone was sufficient to improve ventricular function [126] and maintain circulating blood volume [127] follow ing cardiopulmonary bypass. More recently, a prospective double-blind study involving 234 patients found that amrinone (1.5 mg/kg loading followed by 10 µg· kg -1 ·min -1 infusion) given upon release of aortic cross-clamp was successful in weaning more patients off of the cardiopulmonary bypass as compared with controls (21% vs 7%) [128] .…”
Section: Clinical Applications Of Pde3 Inhibitorsmentioning
confidence: 99%
“…2 Although fluid balance is negative thereafter, BV increases with time. 3 Thus, while BV is an important perioperative measurement in cardiac patients, it has not been reported in those undergoing valve operations. Specific perioperative management for each type of valvular disorder is essential.…”
Section: Introductionmentioning
confidence: 99%